The micronucleated erythrocytes in speeies of Iraqi fish as indieator of dilution (Baghdad Science Journal, 2004)
The micronucleated erythrocytes in fish was used to detect water pollution by genotoxic agents. Fish belonging to different species were collected from three regions from Baghdad during three months (December/2000,January and February/2001 ).The micronucleated erythrocytes was observed in all the specimens. It was concluded that the genotoxic activity' in one region was less than in die other two regions.?